Artificial Intelligence in Pakistan's Cyberspace: Governance Gaps, Dual-Use Dilemmas, and Strategic Vulnerabilities - Sajjad, Ahmed; Ahmad Nizar, Yaakub; Asma, Javed (University of Defence, 2025)
This article examines Pakistan's evolving cyber governance as a critical case of how artificial intelligence (AI) intersects with dual-use security and fragile institutional design. Despite policy commitments, Pakistan's civilian-led cyber architecture remains fragmented, under-resourced and politically volatile, resulting in dependence on military-linked expertise and donor-driven technologies. Drawing on sixteen elite interviews and policymakers, technical experts, and defence strategies, the study identifies five structural vulnerabilities: institutional fragmentation, politicised leadership, underutilised AI infrastructure, civil-military disconnects, and exposure to state-sponsored cyber threats. Framed within dual-use governance and civil-military cyber relations theories, the findings show that Pakistan's insecurity arises less from technological scarcity than from governance dysfunction. The study concludes with policy recommendations from embedding AI within a coherent national doctrine, fostering civil-military integration, and enhancing cyber resilience under the emerging logic of Fifth-Generation Warfare.